Motives for Egyptians hating Achaemenid control (525 - 404 BC) Twenty-seventh family (Journal of the College of Basic Education, 2022)
Egypt, the state and the people, have been subjected to political rivalries to control it since the end of its modern state (1085 BC), and the methods for controlling it have varied, and the peoples that controlled Egypt have also varied, from the rule of strangers to it, such as the Libyan tribes, continuing to the Kushite tribes ( Nubian), which continued until the reign of the last king of her twenty-sixth dynasty (Cinematheel III, 525 BC).This historical period witnessed, in addition to the internal conflicts and revolutions, political competition of another kind, in which the Assyrian state, the Achaemenid state and the Greek state were competing for control of Egypt.The Persian Achaemenids were finally able to control Egypt for the period from (525 BC. AD) until the year (404 BC. AD), when its last king managed to impose his strong control over Egypt for more than a hundred years. The patterns and methods of ruling their kings varied. In this research, we try to identify the position of the Egyptians on the Achaemenid occupation and the nature of the impact of political, economic, social and religious relations among them.